Innovative Teaching Approaches for Improving Students’ Understanding of Map Work by Teachers in South African Schools - Nana Yaw Brenya Agyeman; Nonkula Zenande (ILIN Institute Makassar, 2025)
Despite the efforts of government and education authorities to reform the geography curriculum in order to enhance mapwork teaching and learning, students continue to underperform. The underperformance of students in mapwork remains a major concern for educational authorities, schools, and parents. This study aims to explore innovative instructional approaches used to foster the teaching and learning of mapwork as well as enhance students' understanding of it. A qualitative approach and a case study were used to explore innovative strategies for teaching mapwork. A purposive sample of eight teachers was selected because they had vast experience in teaching geography. Semi-structured interviews were used to collect data. Data was analysed, and themes that emerged from the data were identified. Findings revealed that students struggle to understand mapwork due to an overreliance on traditional methods of instruction. Most teachers struggle to use innovative teaching approaches because of a lack of appropriate resources and online tools to provide practical experiences for students. For mapwork to be effective, schools must provide the necessary resources to improve mapwork instruction and learning and promote a supportive environment. This study contributes to the awareness of the need for schools and teachers to adapt to innovative instructional practices to enhance students' understanding of mapwork. The study recommends that schools provide resources that can assist teachers in effectively facilitating teaching and learning. In addition, teachers should endeavour to use innovative teaching methods.